Pengaruh kekerapan dagangan terhadap kesan pimpin-lengah antara pasaran niagaan kedepan dengan indeks saham di Malaysia - Noor Azuddin Yakob, (Penerbit Universiti Kebangsaan Malaysia, 2005)
The lead-lag effect between stock index futures and stock index has attracted the interest of finance researchers to identify the factors that contributed to the phenomenon. Stock index futures play an important role in the price discovery process since it leads the stock index in responding to new information. This is associated with the problem of stale prices due to the infrequent trading of some inactive component stocks. This paper investigates the influence of infrequent trading towards the existence of lead-lag effect in Malaysia. The result shows that the Composite Index futures contract did not only lead the inactive component stocks but also the active stocks. Such findings contradict the proposed theory because the lead-lag effect prevails among both active and inactive component stocks. Therefore, this study shows that the issue of infrequent trading does not contribute towards the existence of lead-lag effect between stock index futures and stock index in Malaysia